(untitled) (Research, Society and Development, 2021)
An ideal diluent medium for seminal cryopreservation must supply sperm cells with energy, protection and maintenance of an environment suitable for their survival. The objective of this study was to evaluate the in vitro integrity of goat semen cryopreserved in ACP-101c® medium associated with the egg yolk of Numida meleagris, through two techniques of individual sperm cell analysis. Fifteen ejaculates from five goats were collected with the aid of an artificial vagina. Ejaculates were collected in a pool and divided into 12 groups, two control groups: GC1 TRIS, with 2.5% addition of the egg yolk of Gallus gallus domesticus GOGD, GC2 ACP-101c®, with 2.5% addition from the egg yolk of Gallus gallus domesticus GOGD and ten experimental groups GE, containing the addition of the egg yolk of Numida meleagris. Afterwards, the aliquots were bottled in French 0.25 mL straws and frozen with the aid of the TK3000® device and stored in liquid nitrogen. Samples were thawed after seven days and evaluated for DNA integrity and for their individual ultrastructure, using the comet test and transmission electron microscopy, respectively. In the results obtained by the comet test, there was no statistical difference in tail length between the TRIS groups plus GONM, at concentrations of 2.5%, 5% and 10% compared to the control group TRIS 2.5 % of GOGD. There was also no statistical difference regarding the percentage of DNA fragmentation in the tail, in the TRIS groups with 2.5%; 5%; and 20% GONM compared to the TRIS control group 2.5% GOGD (P>0.05). The ACP® groups with 10%, 15% and 20% GONM had greater tail length when compared to the ACP® groups with 2.5% and 5% GONM and control group (ACP® 2.5% GOGD). In the ultrastructural analysis, the ACP® group with 10% GONM stood out with better cellular integrity compared to the other groups, even compared to the evaluated samples of the control group. Thus, it is concluded that the egg yolk of Numida meleagris, as an external membrane cryoprotectant, added to ACP-101c® or TRIS extenders, can reduce the damage caused during the process of cryopreservation of goat semen.